Deciphering Plant-Induced Responses toward Botrytis cinerea and Plasmopara viticola Attacks in Two Grapevine Cultivars Colonized by the Root Biocontrol Oomycete, Pythium oligandrum - Amira Yacoub; Rana Haidar; Ouiza Mesguida; Jonathan Gerbore; Maya Hachicha; Eléonore Attard; Rémy Guyoneaud; Patrice Rey (Journal of Fungi, 2023)
Two major diseases that affect grapevine leaves and berries are controlled by the oomycete Pythium oligandrum. As the efficacy of biocontrol agents strongly depends on factors such as the trophic behaviors of pathogens and cultivar susceptibility, a two-disease approach was implemented to evaluate the activity of P. oligandrum against Botrytis cinerea (the necrotrophic fungus of gray mold) and Plasmopara viticola (the biotrophic oomycete of downy mildew) on two grapevine cultivars with different susceptibilities to these two pathogens. The results show that grapevine root inoculation with P. oligandrum significantly reduced P. viticola and B. cinerea infection on the leaves of the two cultivars, but with differences. This was observed when the relative expression of 10 genes was measured in response to each pathogen, and could be attributed to their lifestyles, i.e., biotrophic or necrotrophic, which are related to the activation of specific metabolic pathways of the plant. In response to P. viticola infection, genes from the jasmonate and ethylene pathways were mainly induced, whereas for B. cinerea, the genes induced were those of the ethylene–jasmonate pathway. The different levels of defense against B. cinerea and P. viticola could also explain the difference in cultivar susceptibility to these pathogens.